A clinical trial of Integra Template for diabetic foot ulcer treatment. Issue 6 (19th October 2015) - Driver, Vickie R.; Lavery, Lawrence A.; Reyzelman, Alexander M.; Dutra, Timothy G.; Dove, Cyaandi R.; Kotsis, Sandra V.; Kim, Hyungjin Myra; Chung, Kevin C.
Abstract: Individuals with diabetes mellitus are at an increased risk of developing a diabetic foot ulcer (DFU). This study evaluated the safety and efficacy of Integra Dermal Regeneration Template (IDRT) for the treatment of nonhealing DFUs. The Foot Ulcer New Dermal Replacement Study was a multicenter, randomized, controlled, parallel group clinical trial conducted under an Investigational Device Exemption. Thirty‐two sites enrolled and randomized 307 subjects with at least one DFU. Consented patients were entered into the 14‐day run‐in phase where they were treated with the standard of care (0.9% sodium chloride gel) plus a secondary dressing and an offloading/protective device. Patients with less than 30% reepithelialization of the study ulcer after the run‐in phase were randomized into the treatment phase. The subjects were randomized to the control treatment group (0.9% sodium chloride gel; n = 153) or the active treatment group (IDRT, n = 154). The treatment phase was 16 weeks or until confirmation of complete wound closure (100% reepithelialization of the wound surface), whichever occurred first. Following the treatment phase, all subjects were followed for 12 weeks. Complete DFU closure during the treatment phase was significantly greater with IDRT treatment (51%) than control treatment (32%; p = 0.001) at sixteen weeks. The median time to complete DFU closure was 43 days for IDRT subjects and 78 days for control subjects in wounds that healed. The rate of wound size reduction was 7.2% per week for IDRT subjects vs. 4.8% per week for control subjects ( p = 0.012). For the treatment of chronic DFUs, IDRT treatment decreased the time to complete wound closure, increased the rate of wound closure, improved components of quality of life and had less adverse events compared with the standard of care treatment. IDRT could greatly enhance the treatment of nonhealing DFUs.